AutoCAD Training and Introduction for JTSB Poliban Students - Suwaji; Anisari, Rezky; Adriyati, Ria; Rafik, Aunur; Ihsani, Abdul Hafizh (Indonesian Journal of Society Development, 2024)
Training and introduction to AutoCAD applications for civil engineering students is an important step in improving students' skills and abilities in using software that is relevant to their field of study. In the implementation of Community Service this time, activities were carried out at the Modeling and Engineering Studio, Civil and Earth Engineering Department, Banjarmasin State Polytechnic on Monday, June 24, 2024. In this training, participants were introduced to the AutoCAD application, tools in the AutoCAD application, and the use and operation of the AutoCAD application in the field of Civil Engineering